Revisiting bronchoscopic intratumoral chemotherapy in malignant central airway obstruction via EUS-B approach and its review of literature - Ram Niwas; Gopal Gopal; Naveen Dutt; Nishant Chauhan (Monaldi Archives for Chest Disease, 2020)
Critical central airway obstruction has always been a dreaded complication to which interventional pulmonologist commonly encounters. There have been various modalities which are used for the management and palliation, which includes mechanical coring, laser, cryoextraction, electrocautery and airway stenting. Rigid bronchoscopy with or without jet ventilation has been corner stone of therapeutics and palliation of central airway obstruction. There are only a few conditions where it is not possible to use rigid bronchoscopy. Here we report a case of metastatic tracheal tumour which presented with critical airway obstruction in a patient who had atlantoaxial instability (AAI) due to rheumatoid arthritis. Here we used endobronchial ultrasound scope (EBUS) via esophageal route, i.e. EUS-B guided approach for sampling of the tracheal tumour, and intratumoral chemotherapy was instilled in multiple sessions, which resulted in shrinking of tumour, thus relieving the critical airway obstruction. This is the first report of using EUS-B approach for intratumoral chemotherapy for tracheal tumors. Bronchoscopic intratumoral chemotherapy therapy (BITC) in tracheal tumors is also one of the options but has not been explored much and there has been a dearth of literature for it.